Staged intervention in a patient with concomitant giant abdominal aortic aneurysm and hepatic artery - Chunyan Zhu; Tong Zhou; Tudi Li; Rong Chen; Zhihuan Zeng (Journal of International Medical Research)
Abdominal aortic aneurysms are the most common types of aneurysms worldwide, whereas aneurysms in the blood vessels of the abdominal organs (splanchnic aneurysms) are rare. Few studies have reported cases of two giant aneurysms occurring simultaneously. Presented here is a case of a 67-year-old man who began to experience periumbilical pain with a diagnosis of a giant abdominal aortic aneurysm and a hepatic artery aneurysm. He was successfully treated using a staged endovascular stent grafting procedure. Postoperatively, the patient’s abdominal pain was resolved, and he was prescribed medication for hypertension control, lipid control, heart rate control, antiplatelet therapy, and smoking cessation, which he took regularly. Follow-up evaluations were performed at 3, 6, and 9 months after surgery, and no late complications were observed. This case report suggests that when two giant aneurysms are diagnosed simultaneously, risk of rupture, surgical interventions, and postoperative complications are significantly increased. The choice of a treatment strategy is complex and has a high degree of individual specificity.